Altered HLA Class I Profile Associated with Type A/D Nucleophosmin Mutation Points to Possible Anti-Nucleophosmin Immune Response in Acute Myeloid Leukemia - Kuželová, Kateřina; Brodská, Barbora; Fuchs, Ota; Dobrovolná, Marie; Soukup, Petr; Cetkovský, Petr (PloS one, 2015)
Nucleophosmin 1 (NPM1) mutations are frequently found in patients with acute myeloid leukemia (AML) and the newly generated sequences were suggested to induce immune response contributing to the relatively favorable outcome of patients in this AML subset. We hypothesized that if an efficient immune response against mutated nucleophosmin can be induced in vivo, the individuals expressing HLA alleles suitable for presenting NPM-derived peptides should be less prone to developing AML associated with NPM1 mutation. We thus compared HLA class I frequencies in a cohort of patients with mutated NPM1 (63 patients, NPMc+), a cohort of patients with wild-type NPM1 (94 patients, NPMwt) and in normal individuals (large datasets available from Allele Frequency Net Database). Several HLA allelic groups were found to be depleted in NPMc+ patients, but not in NPMwt compared to the normal distribution. The decrease was statistically significant for HLA B(*)07, B(*)18, and B(*)40. Furthermore, statistically significant advantage in the overall survival was found for patients with mutated NPM1 expressing at least one of the depleted allelic groups. The majority of the depleted alleles were predicted to bind potent NPM-derived immunopeptides and, importantly, these peptides were often located in the unmutated part of the protein. Our analysis suggests that individuals expressing specific HLA allelic groups are disposed to develop an efficient anti-AML immune response thanks to aberrant cytoplasmic localization of the mutated NPM protein.
Keywords: nukleofosmin; Immunity; peptidy; Leukemia, Myeloid, Acute; lidé; Molecular Sequence Data; akutní myeloidní leukemie; lidé středního věku; Humans; sekvence aminokyselin; Histocompatibility Antigens Class I; Mutation; Middle Aged; jaderné proteiny; Peptides; MHC antigeny I. třídy; analýza přežití; Mutant Proteins; imunita; Case-Control Studies; Survival Analysis; mutace; studie případů a kontrol; mutantní proteiny; Amino Acid Sequence; Nuclear Proteins; Nucleophosmin; molekulární sekvence - údaje